Some Cypriote and Aegean Pottery Recovered from the Shechem Excavations, 1964 - Wright, G. R. H. (1967)
Skrifter utgivna av Svenska Institutet i Athen, 4°, XII / Acta Instituti Atheniensis Regni Sueciae, series in 4°, XII.